2017
DOI: 10.5009/gnl16234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Biliary Drainage without Sphincterotomy in Gallstone Patients with Cholangitis and Suspected Common Bile Duct Stones Not Detected by Cholangiogram or Intraductal Ultrasonography

Abstract: Background/AimsTreatment for cholangitis without common bile duct (CBD) stones has not been established in patients with gallstones. We investigated the usefulness of endoscopic biliary drainage (EBD) without endoscopic sphincterotomy (EST) in patients diagnosed with gallstones and cholangitis without CBD stones by endoscopic retrograde cholangiopancreatography (ERCP) and intraductal ultrasonography (IDUS).MethodsEBD using 5F plastic stents without EST was performed prospectively in patients with gallstones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, it may be difficult or impossible to clear large, multiple, intrahepatic ducts or impacted stones in the CBD by ERCP, and patients with these symptoms can benefit from open CBD exploration (OCBDE) or LCBDE, as these procedures have a high success rate in salvaging such stones [4]. In addition, it has been reported that endoscopic sphincterotomy (EST) may cause duodenobiliary, pancreatic juice and intestinal content reflux that results in recurrent bile duct stone formation, cholecystitis, inflammation in the bile duct, and cholangiocarcinoma [5]. Currently, some experts also suggest that ERCP be applied with appropriate indications in clinical practice.…”
mentioning
confidence: 99%
“…Moreover, it may be difficult or impossible to clear large, multiple, intrahepatic ducts or impacted stones in the CBD by ERCP, and patients with these symptoms can benefit from open CBD exploration (OCBDE) or LCBDE, as these procedures have a high success rate in salvaging such stones [4]. In addition, it has been reported that endoscopic sphincterotomy (EST) may cause duodenobiliary, pancreatic juice and intestinal content reflux that results in recurrent bile duct stone formation, cholecystitis, inflammation in the bile duct, and cholangiocarcinoma [5]. Currently, some experts also suggest that ERCP be applied with appropriate indications in clinical practice.…”
mentioning
confidence: 99%
“…A supporting recommendation is seen in guidance published within the UK two decades ago, and, without a clear consensus to refute this practice, this recommendation is still a common part of definitive management 2 . Conflicting recommendations suggest that sphincterotomy should not be performed in the absence of choledocholithiasis or cholangitis due to the increased risk of the procedure 27 , 28 . Other studies recommend sphincterotomy as definitive treatment in patients who are deemed unfit for cholecystectomy 29 and as an indication for gallbladder drainage 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of short-term cholecystitis after ERCP could be caused by resistance to initial antibiotics on admission[ 29 ], and the incidence of long-term cholecystitis and the recurrence of stones in CBD could be decreased by EPBD compared to EST[ 6 , 12 ]. EST causes significant damages to the Oddi sphincter, and post-EST sphincter dysfunction easily occurs[ 30 ]. Then, the reflux of intestinal contents such as digestive juices, food residue, and bacteria may increase the risk of biliary tract infection and stone recurrence[ 31 , 32 ].…”
Section: Comparison Of Epbd and Estmentioning
confidence: 99%